THE ROLE OF STYLISTICS IN FORENSIC LINGUISTICS: IDENTIFYING AUTHORIAL VOICE AND TEXT AUTHENTICITY - Ashurov Bobir Shakirovich (Modern American Journals, 2025)
This paper examines the role of stylistics in forensic linguistics, particularly its application in identifying authorial voice and establishing text authenticity. Stylistics provides essential tools for analyzing lexical choice, syntactic structures, pragmatic markers, and discourse patterns, which together reveal the distinctive linguistic identity of a writer. In forensic practice, such features are crucial in authorship attribution, plagiarism detection, and the verification of disputed or anonymous documents. The study emphasizes how stylistic markers function as both qualitative and quantitative evidence, offering a linguistic basis for expert conclusions. It further highlights the challenges of variability, intentional disguise, and limited text samples, proposing an integrative approach that combines corpus-based analysis with pragmatic interpretation. Ultimately, forensic stylistics strengthens legal processes by ensuring that judgments concerning authorship and authenticity rest on scientifically informed, transparent linguistic analysis rather than subjective impressions.
Keywords: Stylistics, forensic linguistics, authorship, authenticity, discourse, pragmatics, expertise.